DOI: 10.17077/etd.4lwvy5q8
|View full text |Cite
|
Sign up to set email alerts
|

The Transient Receptor Potential Melastatin 7 is required for early melanophore survival and facets of both embryonic and larval motility in zebrafish

Abstract: The Transient Receptor Potential, Melastatin-like 7 (TRPM7) protein is composed of a long amino terminus, 6 trans-membrane domains, and a carboxy terminal α-kinase domain; TRPM7 tetramers form non-selective cation channels with unusual permeability to Mg 2+. TRPM7 is thought to be expressed in all cell types, and studies conducted primarily on cultured cells have implicated TRPM7 in cellular functions that include cell adhesion, synaptic vesicle release, kidney cation balance, differentiation, survival, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 277 publications
(516 reference statements)
1
1
0
Order By: Relevance
“…We found that mutants had normal electroretinogram waveforms (Decker et al, 2014). It was previously reported that trpm7 mutants have no gross abnormalities in eye morphology (McNeill et al, 2009) and we surmise that mutants most likely have normal visual processing. We also investigated whether locomotor dysfunction in mutants may be impaired by abnormal muscular function.…”
Section: Trpm7 Mutants Exhibit Levo-dopa Responsive Hypomotilitysupporting
confidence: 67%
See 1 more Smart Citation
“…We found that mutants had normal electroretinogram waveforms (Decker et al, 2014). It was previously reported that trpm7 mutants have no gross abnormalities in eye morphology (McNeill et al, 2009) and we surmise that mutants most likely have normal visual processing. We also investigated whether locomotor dysfunction in mutants may be impaired by abnormal muscular function.…”
Section: Trpm7 Mutants Exhibit Levo-dopa Responsive Hypomotilitysupporting
confidence: 67%
“…We used the vmat2 mutant fish to test for a genetic interaction with trpm7. The trpm7 b508 zebrafish display many similarities to vmat2 mutant zebrafish including hypomotility, hypersensitivity to MPP + (Decker et al, 2014), and reduced levels of the neurotransmitters dopamine, norepinephrine, and serotonin (Takahashi et al, 1997) (McNeill et al, 2009. Since the function of vmat2 in dopaminergic neurons is well known and the function of trpm7 in the same neurons is not, we wondered if double mutants would gain us any insight into mechanism by which trpm7 absence leads to dopaminergic neuron dysfunction.…”
Section: Trpm7 Mutants Are Insensitive To Vmat2 Lossmentioning
confidence: 99%